The Effectiveness of a Combination of Slow Breathing Exercises and Progressive Muscle Relaxation on Anxiety Levels in Pre-elderly People with Hypertension - Adit Permana; Upik Rahmi; Ridha Wahdini; Slamet Rohaedi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Pre-elderly individuals often suffer from hypertension, a chronic condition that often causes anxiety due to increased sympathetic nervous system activity. By increasing parasympathetic activity and muscle relaxation, non-pharmacological techniques such as Progressive Muscle Relaxation (PMR) and Slow Breathing Exercises (SBE) have been shown to reduce anxiety levels. Objective: The purpose of this study was to determine the impact of progressive muscle relaxation and slow breathing exercises on anxiety levels in pre-elderly individuals with hypertension in Depok Village, Pakenjeng District, Garut Regency. Methods: This study used a quasi-experimental, non-randomized pre-post-test design with two groups (intervention vs. control). 100 pre-elderly participants were selected using purposive sampling. The intervention lasted for one month and consisted of two 30-minute sessions per week. The Hamilton Anxiety Rating Scale (HARS) was used to assess anxiety symptoms. Results were analyzed statistically using the paired samples t test and the independent samples t test for samples with a significance level of p < 0.05. Results: The results of the study found that after the intervention, anxiety scores in the intervention group decreased significantly from a mean of 27.88 (SD 8.47) to a mean of 12.80 (SD 4.82) (p < 0.001), with a substantial effect size (Cohen's d = 2.21). In the control group, the decrease from a mean of 28.82 (SD 9.10) to a mean of 21.94 (SD 7.18) was less pronounced. A significant difference remained between the two groups after the intervention (mean difference = 9.14; 95% CI: 6.72–11.56; p < 0.001), indicating that the combination of SBE and PMR was effective in reducing anxiety. Conclusion: The combination of slow breathing exercises and progressive muscle relaxation is effective in reducing anxiety levels in pre-elderly people with hypertension. This intervention can be recommended as a non-pharmacological supportive therapy in public health services.